2012
DOI: 10.1371/journal.pone.0047353
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Mass Spectrometry Imaging and Ex Vivo Characterization of Renal Crystalline Deposits Induced in Multiple Preclinical Drug Toxicology Studies

Abstract: Drug toxicity observed in animal studies during drug development accounts for the discontinuation of many drug candidates, with the kidney being a major site of tissue damage. Extensive investigations are often required to reveal the mechanisms underlying such toxicological events and in the case of crystalline deposits the chemical composition can be problematic to determine. In the present study, we have used mass spectrometry imaging combined with a set of advanced analytical techniques to characterize such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…While there obviously room for improvement, the low/high concentration ratios between LC-MS/MS and IR-MALDESI are in fairly good agreement. A correlation between MSI and LC-MS/MS has been demonstrated previously for other ionization methods including MALDI [18, 50, 60-70] and DESI,[22, 71-72] but this is the first example of agreement between IR-MALDESI MSI with LC-MS/MS. Given that LC-MS/MS is a validated quantitation method; the correlation between the average intensities from IR-MALDESI with the absolute quantities determined by LC-MS/MS provides a foundation for quantification directly from an imaging experiment.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…While there obviously room for improvement, the low/high concentration ratios between LC-MS/MS and IR-MALDESI are in fairly good agreement. A correlation between MSI and LC-MS/MS has been demonstrated previously for other ionization methods including MALDI [18, 50, 60-70] and DESI,[22, 71-72] but this is the first example of agreement between IR-MALDESI MSI with LC-MS/MS. Given that LC-MS/MS is a validated quantitation method; the correlation between the average intensities from IR-MALDESI with the absolute quantities determined by LC-MS/MS provides a foundation for quantification directly from an imaging experiment.…”
Section: Resultssupporting
confidence: 73%
“…In some cases the additional knowledge gained from endogenous distributions can provide valuable insight on the impact of the drug on the local environment, implications for site-specific efficacy and toxicity, and can be used to identify certain histological features. [11, 16-18] MSI is befitting to drug discovery and development where the early understanding of preclinical drug distribution (and without requiring a radiolabel) can improve efficiency by narrowing the list of potential candidates.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Nilsson et al demonstrated that compounds administered by inhaled delivery at standard pharmacological dosage can be quantitatively detected by MALDI-MSI, using both MS and MS/MS modes, with acceptable accuracies and precisions [13]. Another study correlated the MALDI-MSI response with quantitative LC-MS/MS performed on adjacent tissue sections and, after harvesting from rats, several single doses of olanzapine at different concentrations [14].…”
Section: Introductionmentioning
confidence: 99%
“…82,112114 Nilsson et al . 112 utilized IMS to examine the accumulation of preclinical crystalline deposits within the kidney, which are common phenotypes of nephrotoxicity that are often difficult to identify.…”
Section: Maldi Imaging Mass Spectrometry: a Molecular Microscope For mentioning
confidence: 99%
“…82,112114 Nilsson et al . 112 utilized IMS to examine the accumulation of preclinical crystalline deposits within the kidney, which are common phenotypes of nephrotoxicity that are often difficult to identify. The administration of 2 potential microsomal prostaglandin E synthase-1 (mPGES-1) inhibitors resulted in multiple signs of renal damage, including increased plasma urea, creatinine, and potassium levels; tubular degeneration/ regeneration; and crystal deposits in rat kidneys.…”
Section: Maldi Imaging Mass Spectrometry: a Molecular Microscope For mentioning
confidence: 99%